Ancient Egypt - Davis, David R. F. (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1997)
This video explores the history and culture of ancient Egypt and also about yhe geography of Egypt and how the Nile River provided the unifying element that gave rise to one of the greatest of the ancient civilizations
Editors, David R. F. Davis, Joseph Sitko
Narrator: Lois La Fond
Keywords: Nile River; Egypt -- History